Aggregate and regional economic effects of new railway infrastructure - Wolfgang Polasek; Wolfgang Schwarzbauer; Richard Sellner (Institute for Advanced Studies (IHS), 2009)
Economists expect positive returns to investments in infrastructure. However a project with higher national returns might have less favourable effects on a regional level than the alternative. Therefore new infrastructure should also be assessed on a regional level, but econom(etr)ic evaluation models are scarce, especially in regional science. This paper proposes new approaches to evaluate infrastructure by a dynamic spatial econometric model that allows long-term predictions. We investigate the regional effects for two Austrian railway projects and show that infrastructure returns are positive on an aggregate and at a regional level but spatial variation can be large.
Keywords: C31; H43; H54; R11; R12; 330; regional growth convergence; traffic accessibility; infrastructure evaluation; spatial econometrics; Schienenstrecke; Infrastrukturinvestition; Regionale Entwicklung; Entwicklungskonvergenz; Schätzung; Österreich